Developing a Maqashid Shariah-Based Green Accounting Model for Forest Fire Mitigation in West Kalimantan - Ningrum, Wulan Wahyu; Hidayat, Samsul; Azimi, Aulia; Jayati, Fitri (Tasharruf: Journal Economics and Business of Islam, 2025)
Forest and land fires in West Kalimantan have become a serious issue with significant ecological and socio-economic consequences, including ecosystem degradation, increased carbon emissions that exacerbate climate change, and health crises caused by toxic haze. Despite government regulations prohibiting land clearing by burning, fires remain frequent, particularly in the palm oil plantation sector. This study aims to explore the potential integration of maqashid sharia-based green accounting as an innovative approach to enhance corporate accountability while supporting sustainable forest fire mitigation. Green accounting incorporates environmental impacts into financial statements, while maqashid sharia provides an ethical foundation for environmental responsibility. Employing a qualitative method with a literature review approach, this research identifies gaps in the application of green accounting within Indonesia’s forestry and plantation sectors. The findings suggest that integrating green accounting and maqashid sharia could offer a comprehensive solution to recurring fires. However, implementation is constrained by inadequate regulation and limited economic incentives for sustainability. This study contributes theoretically by bridging environmental accounting and Islamic ethics, and offers practical implications for policy development. The proposed conceptual model reinforces the role of value-based governance and Islamic ethical principles in advancing environmental accountability, particularly in regions vulnerable to ecological degradation such as West Kalimantan.